Production of jalapeño pepper in mini-tunnel in response to synthetic, organic and carbon fertilization - Ayala Tafoya, Felipe; Encines- Chaidez, Olivia Vanessa; Parra-Delgado, Juan Martín; Valenzuela-López, Marino; López-Urquídez, Guadalupe Alfonso; Yáñez-Juárez, Moises Gllberto (Ecosistemas y Recursos Agropecuarios, 2022)
The use of organic fertilizers in integrated fertilization systems is an alternative for the recovery of soil fertility and raising crop productivity. The research studied the growth and yield of jalapeño pepper plants grown in mini-tunnel, with or without synthetic fertilizers, vermicompost and carbon dioxide from composting. A randomized block design with eight treatments and three replications was used. The variables evaluated were: concentration of carbon dioxide in the internal air of the mini-tunnel; plant height; stem diameter; leaf greenness; dry weight of roots, stems, leaves and total per plant; fruit yield, total and commercial sizes. The data obtained were submitted to the analysis of variance and Tukey test (P ≤ 0.05). Treatments with synthetic fertilizers + vermicompost + CO2/composting (T1), vermicompost + CO2/composting (T5), synthetic fertilizers + CO2/composting (T3), and CO2/composting (T7), increased the concentration of carbon dioxide within the mini-tunnels by 142, 113.8, 78.9 and 66.6%, respectively, compared to the positive control (T4), in which only synthetic fertilizers (378.6 ppm) were used. T1, T2 (synthetic fertilizers + vermicompost) and T3, increased the dry weight per plant in 51.2, 31.1 and 8.4%, and in 50, 24 and 12.1% the total yield, in comparison with the same variables obtained in T4: 104.4 g/plant and 41.2 t ha-1, respectively.
Keywords: Capsicum annuum L.; carbon dioxide; dry weight; fruits yield; leaf greenness